Short Communication: Composition of terpenoid compounds in essential oils extracted from stems of eight Piper species and their role in taxonomic relationships - Laurentius Hartanto Nugroho; ELIZABETH CINDY LEXINTA; YOSEP PRIYONO; RATNA SUSANDARINI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nugroho LH, Lexinta EC, Priyono Y, Susandarini R. 2020. Short Communication: Composition of terpenoid compounds in essential oils extracted from stems of eight Piper species and their role in taxonomic relationships. Biodiversitas 21: 3438-3443. Piper is widely used as source of essential oils from which many bioactive compounds with medicinal properties were used in traditional medicine. The objectives of this study were to explore the chemical composition of essential oils of eight Piper species and to identify its role in determining taxonomic relationships. Chemical composition of essential oils was analyzed using GC-MS analysis on petroleum ether extracts from stems of eight Piper species, while taxonomic relationship was determined using cluster analysis and principal component analysis. Results showed that 21 terpenoid compounds were identified as constituents of the essential oils, consisted of 4 monoterpenes, 14 sesquiterpenes, and 3 diterpenes. The composition of essential oils varied between species. Cluster analysis and principal component analysis showed that differences in the composition of essential oil compounds determined the grouping of species into two clusters. Five compounds were identified as having major role in the grouping of species. These compounds were ?-selinene, ?-caryophyllene, ?-caryophyllene, farnesyl acetone, and ?-amorphene. The results of this study offer opportunities for the use of Piper stems as source of essential oils. This study also confirms the interspecies variability in composition of essential oils, and at the same time supports the use of essential oils in chemotaxonomic studies.